Growth of MoS2–MoO3 Hybrid Microflowers via Controlled Vapor Transport Process for Efficient Gas Sensing at Room Temperature. Issue 10 (8th March 2018) - Kumar, Rahul; Goel, Neeraj; Mishra, Monu; Gupta, Govind; Fanetti, Mattia; Valant, Matjaz; Kumar, Mahesh
Abstract: A nucleation controlled one‐step process to synthesize MoS2 –MoO3 hybrid microflowers using vapor transport process and its application in efficient NO2 sensing at room temperature are reported. The morphology and crystal structure of the microflowers are characterized by scanning electron microscope (SEM), Raman, X‐ray diffraction (XRD), and X‐ray photoelectron spectroscopy techniques. A cathodoluminence mapping reveals that the core of the microflower consists of MoO3, and the flower petals as well as nanosheet are composed of a few layers of MoS2 . Further, the MoS2 –MoO3 hybrid microflower sensor exhibits a high sensitivity of ≈33.6% with a complete recovery to 10 ppm NO2 at room temperature without any extra stimulus like optical or thermal source. Unlike many earlier reports on MoS2 sensor, this advanced approach shows that the sensor is exhibited a low response time (≈19 s) with complete recovery at room tepmerature and excellent selectivity toward NO2 against various other gases. The efficient conventional sensing of the sensor is attributed to a combination of high hole injection from MoO3 to MoS2 and modulation of a potential barrier at MoS2 –MoO3 interface during adsorption/desorption of NO2 . It is believed that the modified properties of MoS2 by such composite could be used for various advanced device applications. Abstract : A simple one‐step process is developed for the synthesis of MoS2 –MoO3 hybrid microflower material system using a conventional chemical vapor deposition process. The superior sensor performances of the material system make it a perfect choice for the fabrication of highly selective room‐temperature NO2 sensor.